Aspek Hukum Pengawasan Pembiayaan Koperasi Syariah Oleh Otoritas Jasa Keuangan dan Kementerian Koperasi dan Usaha Kecil Menengah - Aziza Mutifani Hidayah; Abdul Mujib (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2023)
Sharia cooperatives already resemble Islamic banks, this is motivated by the increasing needs of the community and if there are more choices of financial institutions, it will be easier for the community to determine financing options in sharia institutions. This article examines which is more effective between the OJK and the Ministry of Cooperatives in supervising Islamic Cooperative financing products that resemble Islamic Banks. To solve and answer these problems, researchers used a methodology in the form of a normative approach. This research category is included in library research, namely by using a qualitative descriptive analysis method where the focus of the discussion is on financing in Islamic Cooperatives and Islamic Banks. The author uses primary data sources such as books, archives, and other literature that supports this research. The results of the discussion show that the OJK's supervision of financing carried out by cooperatives that resemble Islamic banks is still not well targeted and evenly distributed, it is more effective if the supervision of Islamic cooperative financing is supervised by the Financial Services Authority, therefore there should be collaboration between the Financial Services Authority and the Ministry of Cooperatives in making policies that are aligned to oversee the implementation of financing in Cooperatives that resemble Islamic Banks, it is necessary to have a memorandum of understanding for the synergy of Cooperative Institutions engaged in financial services and providing financial service products in